The Passions of The Mind: A Biographical Novel of Sigmund Freud - Irving Stone (New York Doubleday & Company Inc., 1971)
Signet 451 - E8789
A Powerful Drama of Sigmund Freud Who Dared to Probe the Nature of Our Sexuality
Keywords: Literature (3GdCOHs; General; Fiction